2021
DOI: 10.3390/foods10010156
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Processing Quality Traits, Protein Content and Composition between Spelt and Bread Wheat Genotypes Grown under Conventional and Organic Production

Abstract: The unique rheological properties of bread wheat dough and the breadmaking quality of its flour are the main factors responsible for the global distribution and utilization of wheat. Recently, interest in the production and expansion of spelt wheat has been boosted due to its significance in the production of healthy food, mostly originated from organic production. The aim of this study was to examine and compare quality parameters (gluten content, Zeleny sedimentation volume, farinograph dough properties), pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 106 publications
4
9
0
Order By: Relevance
“…Protein is the second main component of wheat grain. In our study, spelt wheat varieties showed significantly higher protein content than bread wheat varieties, which is in accordance with the majority of the literature results [ 27 , 47 , 63 , 68 , 70 ]. For example, by analyzing the protein content with three different methods, such as near-infrared spectroscopy, the Dumas method and reverse-phase high-performance liquid chromatography, Call et al [ 71 ] revealed significantly higher protein content in spelt than in bread wheat.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Protein is the second main component of wheat grain. In our study, spelt wheat varieties showed significantly higher protein content than bread wheat varieties, which is in accordance with the majority of the literature results [ 27 , 47 , 63 , 68 , 70 ]. For example, by analyzing the protein content with three different methods, such as near-infrared spectroscopy, the Dumas method and reverse-phase high-performance liquid chromatography, Call et al [ 71 ] revealed significantly higher protein content in spelt than in bread wheat.…”
Section: Discussionsupporting
confidence: 92%
“…In spite of the strong influence of genotype on protein [ 70 ] and starch content [ 101 ], the environment also has a significant effect on both components [ 102 ]. Labuschagne et al [ 103 ] reported that the environment contributed the most to the protein and starch content, followed by the genotype for protein and the G×E interaction for starch content.…”
Section: Discussionmentioning
confidence: 99%
“…001 was observed for seed qualitative characters in all the mutant lines. The seed quality of wheat should be estimated by measuring gluten content, protein content, zeleny sedimentation, and moisture level (Takač et al, 2021).…”
Section: Seed Qualitative Traits Of Three Mutant Generationsmentioning
confidence: 99%
“…In addition to its positive impact on the environment, spelt is also sought after for its unique taste and nutritional benefits. Compared to common wheat, spelt produces seeds with higher protein, lipid, and macro and micronutrient content 2 , 4 , 5 . As a result, spelt grain is used in the production of bread, cookies, pasta, beer, and as a raw material to enrich bakery products 2 .…”
Section: Introductionmentioning
confidence: 99%